Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1998
DOI: 10.1021/jm980299k
|View full text |Cite
|
Sign up to set email alerts
|

Structural Optimization Affording 2-(R)-(1-(R)-3,5-Bis(trifluoromethyl)phenylethoxy)-3-(S)-(4-fluoro)phenyl-4- (3-oxo-1,2,4-triazol-5-yl)methylmorpholine, a Potent, Orally Active, Long-Acting Morpholine Acetal Human NK-1 Receptor Antagonist

Abstract: Structural modifications requiring novel synthetic chemistry were made to the morpholine acetal human neurokinin-1 (hNK-1) receptor antagonist 4, and this resulted in the discovery of 2-(R)-(1-(R)-3, 5-bis(trifluoromethyl)phenylethoxy)-3-(S)-(4-fluoro)phenyl-4-(3-ox o-1 ,2,4-triazol-5-yl)methyl morpholine (17). This modified compound is a potent, long-acting hNK-1 receptor antagonist as evidenced by its ability to displace [125I]Substance P from hNK-1 receptors stably expressed in CHO cells (IC50 = 0.09 +/- 0.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
106
0
1

Year Published

2002
2002
2020
2020

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 205 publications
(117 citation statements)
references
References 32 publications
7
106
0
1
Order By: Relevance
“…In line with this view, we show here that the sustained GFT-inhibiting efficacy of aprepitant reflect its in vivo NK 1 R occupancy in the CNS rather than compound levels of at the site of action. Long-lasting effects of aprepitant in GFT have been reported previously (Hale et al, 1998;Duffy et al, 2002), and the excellent correlation between the sustained GFT inhibition and central NK 1 R occupancy in the present study is also consistent with others (Duffy et al, 2002). The present study, however, extends these findings by demonstrating that prominent GFT-inhibiting efficacy of aprepitant persisted even when its CNS levels were below the limit of detection.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…In line with this view, we show here that the sustained GFT-inhibiting efficacy of aprepitant reflect its in vivo NK 1 R occupancy in the CNS rather than compound levels of at the site of action. Long-lasting effects of aprepitant in GFT have been reported previously (Hale et al, 1998;Duffy et al, 2002), and the excellent correlation between the sustained GFT inhibition and central NK 1 R occupancy in the present study is also consistent with others (Duffy et al, 2002). The present study, however, extends these findings by demonstrating that prominent GFT-inhibiting efficacy of aprepitant persisted even when its CNS levels were below the limit of detection.…”
Section: Discussionsupporting
confidence: 93%
“…The selective NK 1 R antagonists CP-99994 (McLean et al, 1993) and aprepitant (Hale et al, 1998) and the pan-NK receptor antagonist ZD6021 (Bernstein et al, 2001) were synthesized at AstraZeneca (Mölndal, Sweden).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The gene and protein levels of MMP-12, MMP-9, TIMP-1, and NK1R in AMs were detected in the first and second groups, respectively. The same protocols were repeated in the third and fourth groups, with the exception that CP-99,994 was replaced by aprepitant (10 Ϫ8 M; Merck), another NK1R antagonist (18,33) used in clinic (21). The doses of SP, CP-99,994, and aprepitant were chosen because several investigators have shown that they could sufficiently activate or block NK1R in the cells (28,33,56).…”
Section: Methodsmentioning
confidence: 99%
“…More recently, the activation of NK 1 receptors has been linked to the pathoetiology of emesis (Bountra et al, 1993;Beattie et al, 1995;Hale et al, 1998;Rupniak and Kramer, 1999;Diemunsch and Grelot, 2000;Tattersall et al, 2000), pain (Gonzalez et al, 1998;Urban and Fox, 2000), anxiety (Griebel, 1999;Ballard et al, 2001;Cheeta et al, 2001), and depression (Kramer et al, 1998;Maubach et al, 1999). The discovery of nonpeptide, substance P receptor antagonists has led to the development of therapeutic agents for treatment of chemotherapy-induced emesis.…”
mentioning
confidence: 99%